Faktor-Faktor yang Mempengaruhi Penanaman Modal Asing di Indonesia Periode 1997-2023 - Shella Mutia Putri (Bandung Conference Series: Economics Studies, 2024)
Abstract. This study aims to examine the impact of corruption control, market openness, labor productivity, regulatory quality, and minimum wage on foreign direct investment (FDI) in Indonesia. Foreign direct investment (FDI) exerts a profound impact on the macroeconomic and microeconomic landscape of a nation. Corruption control, market openness, labor productivity, regulatory quality, and minimum wage are factors that investors take into account when determining whether to invest funds in a particular country. This research employs quantitative methods with secondary data. The study observed related variables from 1997 to 2023, which were then processed using the least squares method. The results demonstrated that corruption control and minimum wage at the 5% significance level had no effect on FDI, whereas market openness, labor productivity, and regulatory quality at the 5% significance level had an effect on FDI. Abstrak. Penelitian ini bertujuan untuk menguji pengaruh kontrol korupsi, keterbukaan pasar, produktivitas pekerja, kualitas regulasi dan upah minimum terhadap PMA di Indonesia. PMA memiliki pengaruh yang besar baik secara makro maupun mikro ekonomi suatu negara. Kontrol korupsi, keterbukaan pasar, produktivitas pekerja, kualitas regulasi dan upah minimum menjadi pertimbangan investor untuk mengalirkan dana ke suatu negara. Penelitian ini menggunakan metode kuantitatif dengan data sekunder. Penelitian mengamati variabel terkait pada periode 1997 hingga 2023 yang kemudian di olah menggunakan metode least square. Hasil penelitian menunjukkan bahwa kontrol korupsi dan upah minimum pada tingkat signifikansi 5% tidak berpengaruh terhadap PMA sedangkan keterbukaan pasar, produktivitas pekerja dan kualitas regulasi pada tingkat signifikansi 5% berpengaruh terhadap PMA.